2012
DOI: 10.1508/cytologia.77.475
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of the Cytotoxic Effects of Some Pesticides on Soybean (<i>Glycine max</i> L.)

Abstract: SummaryIn this study, the effects of the fungicide Pomarsol Forte WP 80, the insecticide Arrivo 25 EC and the herbicide The End EC were examined for seed germination percentages, the phases of mitosis and chromosomal abnormalities in soybean (Glycine max L.). Median EC (effective concentration) values were calculated according to relative reduction in root length (T/C%) after treatment for 72 h. Germination percentages of primary soybean roots decreased with increasing pesticide concentrations. Cytological obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…They were then squashed in a 1.5% propionic carmine stain in 45% acetic acid (Aksoy and Deveci, 2012). Slides were examined immediately.…”
Section: Mitotic Analysismentioning
confidence: 99%
“…They were then squashed in a 1.5% propionic carmine stain in 45% acetic acid (Aksoy and Deveci, 2012). Slides were examined immediately.…”
Section: Mitotic Analysismentioning
confidence: 99%
“…Many researchers also found that the diferent kinds of species used do not respond similarly to toxic chemicals [22,23]. Seed germination and plant growth bioassays are the most common techniques used to evaluate the toxicity of pesticides [24][25][26][27], heavy metals [6], allelochemicals [28], personal care products [29], compost [30], water samples taken from rivers [31], and industrial waste waters [25,32]. Diferent plant species have also been used such as cucumber and cress [33], letuce and soybean [34], red maple, sugar maple, white pine, and pink oak [35] for phytotoxicity tests.…”
Section: Seed Germination and Root Elongation Testsmentioning
confidence: 99%
“…An additional set of caryopses germinated in distilled water with actively growing roots of at least 2.5 cm in length were placed on Petri dishes and exposed to 500, 1000, 2000 mg L -1 nCeO2 suspensions for 24 h. Ten root tips per each treatment, prepared according to Aksoy and Deveci (2012), were studied to evaluate possible genotoxic effects of nCeO2. According to Mattiello et al (2015), each treatment was replicated three times, for a total of about 10,000 cell observations.…”
Section: Mitotic Indexmentioning
confidence: 99%